2012
DOI: 10.1186/1471-2350-13-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms in survivin gene with the risk of hepatocellular carcinoma in Chinese han population: a case control study

Abstract: BackgroundSurvivin, one of the strongest apoptosis inhibitors, plays a critical role in the development and progression of hepatocellular carcinoma (HCC). By comparison, relatively little is known about the effect of survivin gene polymorphisms on HCC susceptibility. Our study aimed to investigate the association of survivin gene polymorphisms with the risk of HCC in Chinese han population.MethodsA case-control study was conducted in Chinese han population consisting of 178 HCC cases and 196 cancer-free contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 28 publications
0
26
1
Order By: Relevance
“…In recent decades, the prediction and ranking of disease-related miRNAs have received much attention16171819. Experimental verification method for the identification of disease-associated miRNAs is expensive and time-consuming2021.…”
mentioning
confidence: 99%
“…In recent decades, the prediction and ranking of disease-related miRNAs have received much attention16171819. Experimental verification method for the identification of disease-associated miRNAs is expensive and time-consuming2021.…”
mentioning
confidence: 99%
“…However, studies investigating the potential association of these SNPs in survivin gene with tumor risk have not yielded consistent results. Several studies have supported that risk for tumor is associated with these survivin SNPs [17], [19], [36], [38], while others have failed to find such an association [16], [32], [33], [48]. Therefore, we performed the present meta-analysis to clarify the relationship between these survivin SNPs and tumor risk.…”
Section: Discussionmentioning
confidence: 90%
“…As for survivin rs9904341, the ultimate analysis included four gastric cancer studies [28], [29], [30], [31], three hepatocellular cancer studies [20], [32], [33], three colorectal cancer studies [34], [35], [36], two esophageal [18], [37] and two bladder cancer studies [19], [21], as well as twelve studies of other tumors [16], [17], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47]. Overall, 8 studies used Caucasians, 17 used Asians, one used mixed populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, off the three SNPs found using DCL α=108 , two of them are located on the noteworthy genes NISCH and PRKG1. Two previous studies have indicated that SNP rs6784615, found on NISCH, is associated with LOAD [34, 35]. Furthermore, many GWAS studies have found that PRKG1 is also strongly associated with Alzheimer’s disease [36, 37].…”
Section: Discussionmentioning
confidence: 99%